Interpersonal Communication A Mindful Approach to Relationships - Wrench, John S.; Punyanunt-Carter, Narissra M.; Thweatt, Katherine S.; Open Textbook Library (Open Textbook Library, 2020)
Interpersonal Communication: A Mindful Approach to Relationships helps readers examine their own one-on-one communicative interactions using a mindfulness lens. The writing team of Jason S. Wrench, Narissra M. Punyanunt-Carter, and Katherine Thweatt incorporates the latest communication theory and research to help students navigate everyday interpersonal interactions. The 14 chapters in this book cover topics typically taught in an undergraduate interpersonal communication course: family interactions, interpersonal dynamics, language, listening, nonverbal communication, and romantic relationships, as well as exploring emerging areas such as self-compassion, body positivity, friendships, and "the dark side". The writing takes on a purposefully informal tone to engage readers. Each chapter is broken into different sections that have unique instructional outcomes, key takeaways, and exercises, and concludes with real-world case studies and sample quiz questions. Also included is an extensive glossary with over 350 definitions.
Chapter 1: Introduction to Human Communication -- Chapter 2: Overview of Interpersonal Communication -- Chapter 3: Intrapersonal Communication -- Chapter 4: Verbal Elements of Communication -- Chapter 5: Nonverbal Communication -- Chapter 6: Cultural and Environmental Factors in Interpersonal Communication -- Chapter 7: Talking and Listening -- Chapter 8: Building and Maintaining Relationships -- Chapter 9: Conflict in Relationship -- Chapter 10: Friendship Relationships -- Chapter 11: Family & Marriage Relationships -- Chapter 12: Interpersonal Communication in Mediated Contexts -- Chapter 13: Interpersonal Relationships at Work -- Chapter 14: The Dark Side of Interpersonal Communication
In English.
Description based on online resource
Keywords: Academic achievement -- Textbooks; Psychology -- Textbooks